Pengaruh Intensitas Penggunaan Media Tiktok Terhadap Cara Berkomunikasi Mahasiswa Ilmu Komunikasi UINSU - Habib Ardi; Selly Maharani; Fitri Awliyani; Gita Nadia Sihombing; Siti Auliza Fatma Nasution; Ryan Dwi Cahya; Nayla Anindia; Nursapiah Harahap (IAI Nasional Laa Roiba Bogor, 2024)
Today's digital technology has had a significant impact on various aspects of life, such as the use of social media such as TikTok. This platform allows users to react and communicate easily. The presence of TikTok also provides space for users to express and shape their communication patterns. The research was conducted at the North Sumatra State Islamic University with 30 communication science students as subjects. Data was collected through a questionnaire using the Guttman scale. Research findings show that an average of 90% of respondents strongly agree with the positive impact of TikTok in shaping their communication behavior. The analytical method used is descriptive quantitative.